Perhitungan Numerik Kelajuan Lepas Satelit Bumi - Iman Noor; Andry Fitrian; Ahmad Jahrudin (Navigation Physics : Journal of Physics Education, 2022)
A numerical simulation of the Satellites’ orbital velocity and satellites’ escape velocity has been performed. This research aimed to study Satellites’ orbital velocity and orbital escape velocity based on position function. Velocity equation has been gotten from modification equation of centripetal force and equation of earth’s gravitational force. Through the numerical calculation of orbital velocity and escape velocity equation by function discretization, we got that the orbital velocity and escape velocity of the satellite at height of 30.000 km above the earth’s surface are 3.31 km/s and 4.68 km/s, respectively.